ANALISIS ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY ATAS PENGUMUMAN UNUSUAL MARKET ACTIVITY DI BURSA EFEK INDONESIA - Kurniawan, Ari Seta (Jurnal Ilmiah Mahasiswa FEB, 2017)
Unusual market activity (UMA) is an announcement released by the Indonesian Stock Exchange in response to unusual price or volume movement in the traded securities. This research aims to examine the market participants’ reaction toward UMA, as well as the changes of abnormal return and trading volume activity before and after the announcement. The participants’ reaction is poxied by the abnormal return and the trading volume activity. 85 announcements are taken purposively as the research samples from all UMA announcements released during 2013-2015. The observation is conducted for 21 days, including d-day of the announcement. The hypothesis is assessed by means of Wilcoxon test because the samples aren’t normally distributed. The results of the study reveals significant difference of the market reaction around the announcement date. Differernce test results also show a difference of the two aspects before and after UMA Announcement. Keywords: Unusual Market Activity; abnormal return; trading volume activity; studi peristiwa.